2017
DOI: 10.3390/jcs1020012
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Electrical and Thermal Properties in Epoxy/Glass Composites by Graphene-Based Interphase

Abstract: Abstract:Multiscale epoxy/glass composites were fabricated by using E-glass fibers (GF) coated with different types of graphene nanosheets deposited by electrophoretic deposition. Graphene oxide (GO) was first synthesized using modified Hummer's method and its subsequent ultrasonication in de-ionized water created a stable suspension of GO. GF were immersed in the water/GO suspension near a copper anode. The electrical potential applied between the electrodes caused GO to migrate towards the anode. Moreover, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It can therefore be concluded that the samples are characterized by a similar morphology. As documented in a previous paper [45], even when observing the cross sections by SEM, it was not possible to get a reliable measure of the thickness of the rGO layer.…”
Section: Characterization Of the Compositesmentioning
confidence: 92%
See 1 more Smart Citation
“…It can therefore be concluded that the samples are characterized by a similar morphology. As documented in a previous paper [45], even when observing the cross sections by SEM, it was not possible to get a reliable measure of the thickness of the rGO layer.…”
Section: Characterization Of the Compositesmentioning
confidence: 92%
“…It can therefore be concluded that the samples are characterized by a similar morphology. As documented in a previous paper [45], even when observing the cross sections by SEM, it was not possible to get a reliable measure of the thickness of the rGO layer. Thermal stability of the composites was evaluated through thermogravimetric analysis (TGA), and the most important parameters are summarized in Table 4.…”
Section: Also Reports the Values Of Density And Porosity Ofmentioning
confidence: 92%
“…Epoxy matrix composites are one of the most common thermosetting polymers that are widely used because of properties including solvent resistance, thermal stability, and high tensile strength and still new research continues to improve these properties [1][2][3][4][5][6]. These characteristics made epoxy composites to be used in industrial applications such as adhesives, coatings, electronics, encapsulation, and laminates.…”
Section: Introductionmentioning
confidence: 99%
“…Since the polymer matrix essentially needs to resist higher loads, it is normally reinforced with fibers and fillers. Polymer composites reinforced with synthetic fibers made up of glass [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], carbon [21][22][23][24][25][26][27][28][29][30], aramid [31][32][33][34] etc. are being extensively deployed in engineering applications because of their exceptional mechanical performance.…”
Section: Introductionmentioning
confidence: 99%